Analisis Hubungan antara Motivasi dengan Skala Usaha dan Pendapatan Peternak Domba Lokal di Kecamatan Kertajati Kabupaten Majalengka - Mohammad Rifqi Hanafi; Ulfa Indah Laela Rahmah; Aaf Falahudin (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2024)
A research study was conducted in the Kertajati District, Majalengka Regency, to analyze the motivation levels of local sheep farmers and their relationship with business scale and income. The study, which took place from March 8 to April 15, 2023, used a sample of 85 sheep farmers selected through purposive sampling. The analytical methods employed included a survey method with descriptive analysis and rank spearman analysis. The results revealed that the farmers in Kertajati District had a moderate level of motivation towards sheep farming, with exterior factors having the greatest impact on their motivation. There was a strong correlation between motivation and business scale (r = 0.668), indicating a significant relationship. However, the relationship between motivation and income, as well as the relationship between business scale and income, had less meaningful correlations (r = 0.081 and r = 0.069, respectively). In conclusion, the study showed that farmers in the area have a moderate motivation to raise sheep, and there is a significant relationship between motivation and business scale.